Ultrasound stimulated perfluorobutane microbubbles cavitation enhanced the therapeutic effect of colchicine in rats with acute gouty arthritis - Ji-cheng Zhang; Bo Gou; Tian-rui Wang; Wan-tai Dang; Yan-hui Li; Wen Wen; Jian Liu (Heliyon)
Objective: This study aimed to explore whether cavitation generated by ultrasound-stimulated microbubbles (USMB) can enhance the therapeutic efficacy of colchicine and diminish its gastrointestinal side effects in rats with acute gouty arthritis (AGA). Materials and methods: The rat AGA model was established by injection of Monosodium urate (MSU) crystals. The rats were randomly divided into 6 groups (A: control group, B: model control group, C: cavitation group, D: high dose colchicine group, E: cavitation + low dose colchicine group, F: cavitation + high dose colchicine group) according to whether they were given cavitation and different doses of colchicine. The effect of cavitation on blood perfusion was analyzed by comparing contrast-enhanced ultrasound (CEUS) and the area under the curve (AUC) of CEUS with the ankle joint of right hind limb. The AGA symptoms were assessed by referring to the degree of ankle joint swelling within 24 h and the gait score. The infiltration of neutrophils was determined using the hematoxylin-eosin (HE) staining method. For the evaluation of vascular inflammation and dilation, plasma interleukin-1β (IL-1β) and endothelial nitric oxide synthase (eNOS) served as the key indicators. Besides, the severity of gastrointestinal adverse reactions is determined by analyzing the gastrointestinal reaction scores. Results: When compared with groups A, B, and D, the AUC was markedly higher in groups C, E, and F (all P < 0.05). In groups E and F, the degree of ankle swelling, gait scores, and the level of plasma IL-1β in AGA rats were lower, while the concentration of plasma eNOS was higher compared to the group D (all P < 0.05). HE staining findings demonstrated that the integration of cavitation and colchicine played a positive role in reducing neutrophil infiltration in the ankle joint synovium and mitigating the gastrointestinal reaction score in AGA rats. In contrast to groups D, E, and F that were given colchicine, group E had a substantially lower gastrointestinal reaction score, with statistically significant differences observed in pairwise comparisons (all P < 0.05). Conclusion: In rats with AGA, cavitation generated by USMB exerted a remarkable effect on augmenting the blood perfusion of the ankle joint. This, in turn, not only amplified the anti-gout efficacy of colchicine but also reduced the dosage of colchicine. Concurrently, it effectively mitigated the associated gastrointestinal side effects.